Digital Democracy in Post‑2024 Indonesia: Between Expanded Participation and Normalized Polarization - Priyono, Setyo Hari (Department of Sociology, Universitas Nasional (Indonesia), 2026)
This article examines the ambivalent trajectory of Indonesia’s digital democracy after the 2024 national elections, focusing on how digitalization reshapes participation, public discourse, and electoral governance. Using a qualitative descriptive, literature‑based design, the study synthesizes international meta‑analyses on digital media and participation, research on digital inclusion and critical digital literacy, and Indonesian evidence from academic studies, official reports, and civil society monitoring. The findings show that social media and online platforms have expanded information access and expressive political engagement, especially among younger citizens, yet participation remains socially stratified and often shallow, mirroring global patterns of participation bias. Furthermore, industrialized disinformation, buzzer networks, and emerging uses of AI‑generated content erode epistemic quality and trust, while regulatory and supervisory responses by electoral bodies remain fragmented and formalistic. Therefore, the article argues for structural reforms that combine digital inclusion, critical digital literacy, and platform governance. Future research needs to focus on buzzer ecosystems, AI‑mediated campaigning, and digital intraparty democracy.